TINDAK KEJAHATAN GENOSIDA TERHADAP ETNIS ROHINGYA DI NEGARA MYANMAR DALAM PERSPEKTIF HUKUM PIDANA INTERNASIONAL - Musfiroh, Musfiroh; Safiulloh, Safiulloh; Rukmana, Bella Shintia (LPPM Universitas Bina Bangsa, 2024)
The Rohingya ethnic group is a community that lives in the Arakan region of the state of Myanmar. This ethnic group experiences problems in terms of citizenship. The Rohingya ethnic group did not have citizenship starting from the enactment of the 1864 Foreign Countries Act, the 1948 Myanmar Citizenship Act drawn up by the British government. And the peak occurred when the Myanmar citizenship law was implemented in 1982. In this law it was stated that the ethnic groups recognized as Myanmar citizens were those who had ancestors and lived in Rohingya since 1823. The Myanmar government assumes that the Rohingya ethnic group are immigrants. black people who come from Bangladesh because of the similar physical characteristics of the Rohingya ethnic group and the Bengali ethnic group. As a result of the lack of citizenship status, the Rohingya ethnic group is not under the protection of a state, resulting in many human rights violations. The impact of human rights violations in the form of torture and murder and the carrying out of military operations by the Myanmar government was the occurrence of several massive waves of refugees leaving the Arakan area. Conditions in the Arakan region heated up again in 2012, this led to oppression, torture and murder causing Rohingya residents to flee to several surrounding countries such as Bangladesh, Thailand, Malaysia and Indonesia. The problem raised in this research is that the actions carried out by Myanmar constitute a crime of genocide. This research aims to describe and analyze international criminal law regulations regarding violence that occurred against the Rohingya ethnic group in Myanmar, whether it can be categorized as an international crime or not, and to find out and analyze how to resolve cases of serious human rights violations against the Rohingya ethnic group in the country. Myanmar is based on international criminal law. This type of research uses normative legal research. The materials used are primary, secondary and tertiary materials obtained from literature studies. The research results show that violence against the Rohingya ethnic group in Myanmar is an international crime which is classified as serious and is under the jurisdiction of the international criminal court and can be sanctioned in accordance with international criminal law